A study of the Manhattan city water works - Swanson, Ernest Felix (My University, 1906)
Introduction: In making a study of the municipal ownership of the water supply of a small city, drawbacks are encountered in that suitable statistics are hard to procure. Accounts are kept with little attempt at proper classification. Many items are placed under general heads such as "maintenance" and "miscellaneous". Under these heads are listed one fourth of all expenditures incurred by the city water works of Manhattan. This ambiguous method of keeping books may be sufficient for ascertaining the loss and gain of the whole, but is certainly most unsatisfactory from the standpoint of the investigator into all the details of administration. Neither is it business-like nor safe. In spite of this disadvantage sufficient data have been secured upon which to base a discussion that will justify the conclusion herein reached. My efforts in this line have been greatly facilitated by the hearty cooperation of the city clerk and the free access to all his books, memoranda, and accounts. Valuable assistance was also rendered by several worthy citizens of the town. Criticisms offered are not intended to be personal, but merely to turn on the light where it is needed and to be suggestive of needed improvements. In making a study of the plant in which the citizens of Manhattan are interested, we find that in accordance with the laws of the State of Kansas providing for the construction and maintenance of municipal water works systems, the citizens of Manhattan in 1886, then a city of about 2700 inhabitants began to agitate the question of installing a system of water works, and a special election on March 24th of the following year, for the purpose of issuing bonds for the same.
Citation: Swanson, Ernest Felix. A study of the Manhattan city water works. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Public Water System; Municipal Water Works; Manhattan; Kansas; Theses